1999
DOI: 10.1074/jbc.274.50.35703
|View full text |Cite
|
Sign up to set email alerts
|

Separate Cis-acting DNA Elements Control Cell Type- and Tissue-specific Expression of Collagen Binding Molecular Chaperone HSP47

Abstract: HSP47 is a collagen-binding heat shock protein and is assumed to act as a molecular chaperone in the biosynthesis and secretion of procollagen. As the synthesis of HSP47 is closely correlated with that of collagen in various cell lines and tissues, we performed a promoter/ reporter assay using HSP47-producing and nonproducing cells. 280 base pairs (bp(s)) of upstream promoter were shown to be necessary for the basal expression but not to be enough for the cell type-specific expression. When the first and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
17
0
2
Order By: Relevance
“…Procollagen polypeptides form a complex with HSP47 in the endoplasmic reticulum, which plays an important role as a collagen-specific molecular chaperone in the intracellular processing/folding of procollagen molecules (23,24). The crucial role of HSP47 in regulating biosynthesis of collagen molecules has been reported previously (25), and transcriptional regulation for HSP47 expression was clarified (26,27). However, its role in kidney diseases in relation to sclerosis/ fibrosis in diabetic nephropathy and IgA nephropathy is completely unknown.…”
Section: Quantitation Of the Expression Ratio Of Hsp47/gapdh Mrna Andmentioning
confidence: 99%
“…Procollagen polypeptides form a complex with HSP47 in the endoplasmic reticulum, which plays an important role as a collagen-specific molecular chaperone in the intracellular processing/folding of procollagen molecules (23,24). The crucial role of HSP47 in regulating biosynthesis of collagen molecules has been reported previously (25), and transcriptional regulation for HSP47 expression was clarified (26,27). However, its role in kidney diseases in relation to sclerosis/ fibrosis in diabetic nephropathy and IgA nephropathy is completely unknown.…”
Section: Quantitation Of the Expression Ratio Of Hsp47/gapdh Mrna Andmentioning
confidence: 99%
“…The plasmid pact-␤-galactosidase, which bears the chicken ␤-actin promoter upstream of lacZ, was used as an internal control to normalize transfection efficiency. ␤-Galactosidase assays were performed as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…However, the cell type-specific expression of hsp47 could not be attributed to this promoter region alone. Hirata et al (15) also showed that the first two introns, located upstream of the translation initiation site, are necessary in addition to the 280-bp promoter region for the tissuespecific expression of hsp47. Considering these previous results, we made systematic deletion constructs fused to the luciferase gene to identify the cis-acting element(s) in the first and the second introns that are responsible for the constitutive expression of hsp47.…”
Section: Identification Of Cis-acting Elements In Hsp47 Introns Thatmentioning
confidence: 99%
See 2 more Smart Citations